# If pn= pn-1 +4 and p17=74, then p3=

QUESTION POSTED AT 26/03/2020 - 01:05 PM

QUESTION POSTED AT 26/03/2020 - 01:05 PM

**Your answer is p3=18**

Hello :

2x-3y=6 ...(1)

-3y=-2x+6

y =2/3 x-2..... the slope of a line parallel to the line 2x-3y=6 is : 2/3 (same slope)

2x-3y=6 ...(1)

-3y=-2x+6

y =2/3 x-2..... the slope of a line parallel to the line 2x-3y=6 is : 2/3 (same slope)

ANSWERED AT 29/03/2020 - 06:27 PM

QUESTION POSTED AT 29/03/2020 - 06:27 PM

Hello :

1) 2x-3y=6

3y =2x-6

y =(2/3)x-2.......(answer : A) 2/3 )

2) 4x-9y= -36

9y =4x+36

y = 4/9x +4 .......( answer : C) y=4/9x+4 )

3) answer : C) (x+2)=3(y-1)

the slope is : 3 and passing by (-2,1)

1) 2x-3y=6

3y =2x-6

y =(2/3)x-2.......(answer : A) 2/3 )

2) 4x-9y= -36

9y =4x+36

y = 4/9x +4 .......( answer : C) y=4/9x+4 )

3) answer : C) (x+2)=3(y-1)

the slope is : 3 and passing by (-2,1)

ANSWERED AT 29/03/2020 - 06:20 PM

QUESTION POSTED AT 29/03/2020 - 06:20 PM

No graphs are shown......

ANSWERED AT 28/03/2020 - 12:59 PM

QUESTION POSTED AT 28/03/2020 - 12:59 PM

You would multiply 6 by both, the x and the 4 to get your answer.

6(x+4)

6*x+6*4=

6x+24

6(x+4)

6*x+6*4=

6x+24

ANSWERED AT 28/03/2020 - 12:43 PM

QUESTION POSTED AT 28/03/2020 - 12:43 PM

2x + 4

If x = 45

2 (45) + 4

= 90 + 4

= 94

If x = 45

2 (45) + 4

= 90 + 4

= 94

ANSWERED AT 28/03/2020 - 12:05 PM

QUESTION POSTED AT 28/03/2020 - 12:05 PM

Hello:

y=(1/8)x+b

the line that passes through (0, 5) :5 = (1/8)(0)+b

b = 5

the equation is : y = (1/8)x+5

ANSWERED AT 28/03/2020 - 11:37 AM

QUESTION POSTED AT 28/03/2020 - 11:37 AM

**Answer:**

1) D. distributive property

2) C. D=all real numbers; R = {y | y ≥ 0}

**Step-by-step explanation:**

**1)** We observe that the factor of -4 has been multiplied by each of the terms of the binomial in parentheses. This is an application of the ** distributive property**.

__

**2)** Any polynomial has a domain of ** all real numbers**. The range of an even-degree polynomial will be limited by its extreme value. Here, the vertex of this quadratic function is (1, 0), so the range is

F(x) = x^2 -2x +1 = (x -1)^2

Any square will have a minimum value of 0. For this function, that occurs at ...

(x, y) = (1, 0)

The range will be values of y equal to or greater than zero.

ANSWERED AT 28/03/2020 - 11:36 AM

QUESTION POSTED AT 28/03/2020 - 11:36 AM

Solución 1: 2(x) + 3(y) = 80

solución 2: 3(x) + 2(y) = 70

3(y) + 2(x) = 80

2(y) + 3(x) = 70

2y = -3x + 70

y = -3x÷2 + 35

2x + 3(-3x÷ 2+35) = 80

-5x÷2 = -25

-5x = -50

5x = 50

x-intercept: 10

x = 10

y = -3x÷ 2+35

y = -(3÷2)(10)+35 = 20

x-interpcet: 10

y-intercept: 20

~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~

solución: x - 8y = 0

solución x + 4y = 480

-8y + x = 0

4y + x = 480

x-intercept (solución 2)

x = -4x + 480

x-intercept (solución 1)

4y + 180 - 8y = 0

-12y = 480

y-intercept: 40

x-intercept: 320

Buena Suerte!

solución 2: 3(x) + 2(y) = 70

3(y) + 2(x) = 80

2(y) + 3(x) = 70

2y = -3x + 70

y = -3x÷2 + 35

2x + 3(-3x÷ 2+35) = 80

-5x÷2 = -25

-5x = -50

5x = 50

x-intercept: 10

x = 10

y = -3x÷ 2+35

y = -(3÷2)(10)+35 = 20

x-interpcet: 10

y-intercept: 20

~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~

solución: x - 8y = 0

solución x + 4y = 480

-8y + x = 0

4y + x = 480

x-intercept (solución 2)

x = -4x + 480

x-intercept (solución 1)

4y + 180 - 8y = 0

-12y = 480

y-intercept: 40

x-intercept: 320

Buena Suerte!

ANSWERED AT 28/03/2020 - 11:14 AM

QUESTION POSTED AT 28/03/2020 - 11:14 AM

The width is 73, (73w)

ANSWERED AT 28/03/2020 - 10:31 AM

QUESTION POSTED AT 28/03/2020 - 10:31 AM

X^2 + 4 = 0

Using the square root method, subtract 4 from both sides.

x^2 = -4

To clear the power of 2, take the square root of both sides.

x = + - square rot of (-4)

x = + - 2i

This is a complex answer because the radicand was a negative number.

x^2 - 6x + 1 = 0

I would use completing the square to solve this problem.

Subtract 1 from both sides.

x^2 - 6x = -1

When completing the square, take the b term (-6) and divide by 2 (-6/2= -3),

then square this number (9), add the number to both sides.

x^2 - 6x + 9 = -1 + 9

The left side is now a perfect square trinomial.

(x - 3)^2 = 8

To clear the power of 2, take the square root of both sides.

x - 3 = + - sqrt 8

add 3 to both sides and simplify sqrt 8

x = 3 + - 2sqrt2

Using the square root method, subtract 4 from both sides.

x^2 = -4

To clear the power of 2, take the square root of both sides.

x = + - square rot of (-4)

x = + - 2i

This is a complex answer because the radicand was a negative number.

x^2 - 6x + 1 = 0

I would use completing the square to solve this problem.

Subtract 1 from both sides.

x^2 - 6x = -1

When completing the square, take the b term (-6) and divide by 2 (-6/2= -3),

then square this number (9), add the number to both sides.

x^2 - 6x + 9 = -1 + 9

The left side is now a perfect square trinomial.

(x - 3)^2 = 8

To clear the power of 2, take the square root of both sides.

x - 3 = + - sqrt 8

add 3 to both sides and simplify sqrt 8

x = 3 + - 2sqrt2

ANSWERED AT 28/03/2020 - 10:29 AM

QUESTION POSTED AT 28/03/2020 - 10:29 AM

I would go with C because it seems like the only legitimate equation I can come up with for this question. Hope I helped you out!

ANSWERED AT 27/03/2020 - 12:43 PM

QUESTION POSTED AT 27/03/2020 - 12:43 PM

The answer is c not d not a and not b

ANSWERED AT 27/03/2020 - 10:11 AM

QUESTION POSTED AT 27/03/2020 - 10:11 AM

X= 1 .........................

ANSWERED AT 27/03/2020 - 09:41 AM

QUESTION POSTED AT 27/03/2020 - 09:41 AM

Let's isolate x by moving the -1 to the left and the 3/2x to the right (direction chosen so that you don't get negative numbers):

Now multiply both sides by 2 and swap sides:

Now multiply both sides by 2 and swap sides:

ANSWERED AT 26/03/2020 - 09:03 PM

QUESTION POSTED AT 26/03/2020 - 09:03 PM

Remember, you can do anything to an equation as long as you do it to both sides

get 1 of the x on one side

5x-14=8x+4

minus 5x both sides (we want on left side because 8>5 and I like positive stuff)

5x-5x-14=8x-5x+4

0-14=3x+4

-14=3x+4

minus 4 both sides

-14-4=3x+4-4

-18=3x+0

-18=3x

divide both sides by 3

remember, negative/positive=negative

-18/3=(3x)/3

-6=x(3/3)

-6=x(1)

-6=x

x=-6

get 1 of the x on one side

5x-14=8x+4

minus 5x both sides (we want on left side because 8>5 and I like positive stuff)

5x-5x-14=8x-5x+4

0-14=3x+4

-14=3x+4

minus 4 both sides

-14-4=3x+4-4

-18=3x+0

-18=3x

divide both sides by 3

remember, negative/positive=negative

-18/3=(3x)/3

-6=x(3/3)

-6=x(1)

-6=x

x=-6

ANSWERED AT 26/03/2020 - 01:57 PM

QUESTION POSTED AT 26/03/2020 - 01:57 PM

55X add them all up and add x

ANSWERED AT 26/03/2020 - 12:48 PM

QUESTION POSTED AT 26/03/2020 - 12:48 PM

I think this is the answer you are looking for. I hope this helps.

ANSWERED AT 26/03/2020 - 12:41 PM

QUESTION POSTED AT 26/03/2020 - 12:41 PM

The roots of a polynomial are the values that render the polynomial to zero

y=(x+4)(x-2)^2(x+7)

in the 1st parenthesis, x=-4 render the polynomial =0

in the 2nd parenthesis, x=2 render the polynomial =0

in the 3rd parenthesis, x=-7 render the polynomial =0

So there are 3 values as roots of this polynomial (answer C)

y=(x+4)(x-2)^2(x+7)

in the 1st parenthesis, x=-4 render the polynomial =0

in the 2nd parenthesis, x=2 render the polynomial =0

in the 3rd parenthesis, x=-7 render the polynomial =0

So there are 3 values as roots of this polynomial (answer C)

ANSWERED AT 26/03/2020 - 12:25 PM

QUESTION POSTED AT 26/03/2020 - 12:25 PM

3x + 2y = 4

subtract 3x from both sides

2y = -3x + 4

divide both sides by 2

y = -3/2x + 2

LETTER A

subtract 3x from both sides

2y = -3x + 4

divide both sides by 2

y = -3/2x + 2

LETTER A

ANSWERED AT 26/03/2020 - 10:35 AM

QUESTION POSTED AT 26/03/2020 - 10:35 AM

The last one is no solutions and the first on is infinitely many solutions
and the second one is one solution. I am pretty sure! Hope this helps!

ANSWERED AT 26/03/2020 - 07:36 AM

QUESTION POSTED AT 26/03/2020 - 07:36 AM

3x + 4y = 12

To find x subtract 4y from both sides

3x = 12 - 4y

Then divide all terms by 3

3x/3 = 12/3 - 4y /3

So, x = 4 - 4/3y

To find x subtract 4y from both sides

3x = 12 - 4y

Then divide all terms by 3

3x/3 = 12/3 - 4y /3

So, x = 4 - 4/3y

ANSWERED AT 26/03/2020 - 06:23 AM

QUESTION POSTED AT 26/03/2020 - 06:23 AM

5(2x-5)(5x+4) = 0

2x-5 = 0

2x = 5

x = 5/2 (Answer)

5x+4 = 0

5x = -4

x = -4/5 (Answer)

2x-5 = 0

2x = 5

x = 5/2 (Answer)

5x+4 = 0

5x = -4

x = -4/5 (Answer)

ANSWERED AT 26/03/2020 - 05:59 AM

QUESTION POSTED AT 26/03/2020 - 05:59 AM

3x+4=8

Want to isolate x so subtract 4 from both sides the equation is now

3×=4

Then divde both sides by 3 to get x by itself the equation is now

X=4/3

So x is equal to 4/3

(Give 22chocolate22 Brainliest)

Want to isolate x so subtract 4 from both sides the equation is now

3×=4

Then divde both sides by 3 to get x by itself the equation is now

X=4/3

So x is equal to 4/3

(Give 22chocolate22 Brainliest)

ANSWERED AT 26/03/2020 - 05:17 AM

QUESTION POSTED AT 26/03/2020 - 05:17 AM

**Answer:**

**Step-by-step explanation:**

We know that the vertex of the parabola is

That means this points is being intercept by the parabola. In other words, the function that represents this parabola has to have this relation, when , .

So, you can observe that the second choice has a function that follows this relation. Let's see

So, for

Therefore, function B is the answer because it includes the vertex at its relation.

ANSWERED AT 26/03/2020 - 04:08 AM

QUESTION POSTED AT 26/03/2020 - 04:08 AM

**Answer:**

3) D: The vertex, in this case N (as the middle point) needs to be in the middle of the name.

4) C: These triangles are reflection of each other, if you would place them in front of a mirror, this would be the only one true.

5) A: According to the picture, the angles are the same, so what will be missing is to know if the hypotenuse is the same, as we already know that one side is the same (perpendicular one), therefore we already have S(side), A (angle), missing side (S) for it to be solved by SAS.

6) A: ASA postulate says that you need one angle (A1), the side between A1 and A2, and a second angle (A2), which corresponds to tha description.

7) missing the picture

8) B: 65. Two of the angles are 90 and the other one is 125. Within any quadrilateral the sum of angles must be 360. Therefore m=360-90-90-125=65.

**Step-by-step explanation:**

ANSWERED AT 26/03/2020 - 03:03 AM

QUESTION POSTED AT 26/03/2020 - 03:03 AM

I think the answer might be D hope this helps

ANSWERED AT 26/03/2020 - 02:49 AM

QUESTION POSTED AT 26/03/2020 - 02:49 AM

9/27, 12/27, 16/27

So this is a geometric sequence as each term is 4/3 the previous term.

Since the common ration is greater than one the sum of the series diverges, it does not exist. (The sum just keeps getting larger and larger)

For a geometric series to have a sum r^2<1

So that the normal sum....

s(n)=a(1-r^n)/(1-r) becomes if r^2<1

s=a/(1-r)

So this is a geometric sequence as each term is 4/3 the previous term.

Since the common ration is greater than one the sum of the series diverges, it does not exist. (The sum just keeps getting larger and larger)

For a geometric series to have a sum r^2<1

So that the normal sum....

s(n)=a(1-r^n)/(1-r) becomes if r^2<1

s=a/(1-r)

ANSWERED AT 26/03/2020 - 02:43 AM

QUESTION POSTED AT 26/03/2020 - 02:43 AM

Lets make the equation in y = form

3x+4y=12

subtract 3x from both sides

4y=-3x+12

divide both sides by 4

y=-3/4x+3

this lines slope is -3/4

a perpendicular line has a slope that is opposite the sign (+/-) and is flipped

the perpendicular lines slope will be 4/3

3x+4y=12

subtract 3x from both sides

4y=-3x+12

divide both sides by 4

y=-3/4x+3

this lines slope is -3/4

a perpendicular line has a slope that is opposite the sign (+/-) and is flipped

the perpendicular lines slope will be 4/3

ANSWERED AT 26/03/2020 - 02:15 AM

QUESTION POSTED AT 26/03/2020 - 02:15 AM

Simplify the expression first by the "flip and multiply" method. We end up first with:

[x(x-3)]/[x⁻¹(x+4)]

Simplifying further we have:

[x²(x-3)]/(x+4)

Solving for restriction we equate the denominator to 0:

x + 4 = 0

x = -4

x≠4 (-4 is a restriction of the expression)

[x(x-3)]/[x⁻¹(x+4)]

Simplifying further we have:

[x²(x-3)]/(x+4)

Solving for restriction we equate the denominator to 0:

x + 4 = 0

x = -4

x≠4 (-4 is a restriction of the expression)

ANSWERED AT 21/03/2020 - 11:22 AM

QUESTION POSTED AT 21/03/2020 - 11:22 AM